Mechanical methods for state determination of Lithium-Ion secondary batteries: A review. (December 2020) - Popp, Hartmut; Koller, Markus; Jahn, Marcus; Bergmann, Alexander
Highlights: Foremost comprehensive review on mechanical methods for SOX determination (LIB). Non-destructive in-situ & in-operando detection of battery's performance. Emphasis on sensor techniques integration into imminent commercial batteries. Comparative study on scale, cost, complexity & boundaries of each mechanical method. Industrialization of smart Lithium-Ion batteries for BMS sensorics of the future. Abstract: Lithium-Ion batteries are the key technology to power mobile devices, all types of electric vehicles, and for use in stationary energy storage. Much attention has been paid in research to improve the performance of active materials for Lithium-Ion batteries, however, for optimal, long and safe operation, detailed knowledge of -among others- the state-of-charge and the state-of-health of the battery is paramount both in laboratory use, as well as during application by the battery management system. Today's systems often derive their estimators from data of the voltage, current and temperature measurements, which can lead to inaccurate estimations of values during operation. Mechanical based measurements became very popular recently to fill the gap in data by complementing conventional measurements and thus provide more accurate information about the internal state of Lithium-Ion batteries. This review aims to present the current state of this promising topic for both laboratory use and applications on non-destructive in-situ and in-operando methods for measurement of mechanical battery parameters like expansion, strain and force, experimental modal analysis, ultrasonic probing and acoustic emission technologies. The intention of this summary is to provide insights in this emerging topic by showing benefits, drawbacks, possibilities and applications of each technique and compare those to each other, thus providing the readers with a deep insight into the topic.